Profile and evolution of intensive care nurses' education as potentiators of Science (Research, Society and Development, 2020)
The present study aims to investigate the professional training profile of intensive care nurses in a teaching hospital through a descriptive, exploratory study, with a quantitative methodological approach. Twenty nurses working in an intensive care unit in a teaching hospital located in the state of Rio de Janeiro participated in the study. The data were collected through a structured questionnaire, and analyzed using the statistical program Action pro®, using mean, standard deviation, absolute and relative frequency. Most nurses were not admitted sequentially to graduation and presented, in the vast majority, knowledge in the clinical area. There was also an increase in professional masters in nursing and a low investment of nurses' time in the education discipline, even working in a university education scenario, where he is responsible for the training of neophytes from different disciplines. Therefore, it is considered that nursing must prioritize different areas of interest in science, mainly to develop transdisciplinary skills, to contribute to the evolution of nursing as a science.